ANALISIS PROBLEMATIKA KOMISI PEMILIHAN UMUM KOTA JAMBI DALAM UPAYA PEMENUHAN HAK POLITIK BAGI PEMILIH TUNAWISMA PADA PEMILIHAN UMUM TAHUN 2024 DI KOTA JAMBI - Riska Dewi Anggraeni; Ian Pasaribu; Revi JeanePutri; Mariatul Qibtyah (Halu Oleo University, 2025)
This study aims to determine the problems or issues faced by the Jambi City General Election Commission (KPU) in its efforts to fulfil the political rights of homeless voters in the 2024 Election. This study uses Taupiqurrahman's inclusive political theory framework, which emphasises accessibility, representation, equality of rights and protection, participation, and political education as the basis for analysing the fulfilment of the political rights of homeless voters. This study uses a descriptive qualitative method. The results of the study indicate that the problems faced by the Jambi City KPU in fulfilling the political rights of the homeless include difficulties in data collection due to not having a permanent place of residence and minimal ownership of population documents. This has an impact on the low accessibility of homeless voters in the election process and causes them not to be registered as legitimate voters. In addition, the lack of socialisation and political education targeting homeless groups also has an impact on their low participation. Other findings also show that homeless voters still face inequality of rights compared to different voter groups. On the other hand, administrative and operational constraints also limit the KPU in its efforts to fulfill the political rights of the homeless, including the lack of special regulations, uneven socialization, and the absence of cross-sector coordination to ensure that the political rights of homeless voters can be optimally fulfilled, these problems also hinder efforts for political inclusivity have not been realized.